Impact of Cash Transfers Programme on Agricultural Production in Kenya: Focus on the Orphans and Vulnerable Children - Ndolo, David Katuta (European Scientific Journal, ESJ, 2023)
Orphans and children from low-income households are particularly vulnerable to the negative effects of a growing wealth gap since they are already at the bottom of the social ladder. Most of these households are found in rural areas and are engaged in farming. Governments may use programs like cash transfers (CTs) to cushion the impact of economic uncertainty on the poor. Following the introduction of the cash transfer program for orphans and vulnerable children in Kenya, this research aimed to analyze the impact of cash transfers on agricultural output and labor supply. Based on a difference-in-differences estimate, the study found that orphans and vulnerable children’s families who received cash transfers had an increase in agricultural output of 8.5%. Spending on labor supply and hiring employees for agricultural operations by Orphans and Vulnerable Children households increased by 121% after the program was implemented, compared to households headed by non-Orphans and Vulnerable Children. These findings provide more evidence that governments should take action to increase direct and indirect cash transfers to disadvantaged populations like orphans, suggesting that Cash transfers have a major influence on their quality of life.